2004
DOI: 10.3141/1881-04
|View full text |Cite
|
Sign up to set email alerts
|

Basis of the Swiss Design Standard for Roundabouts

Abstract: The roundabout form of intersection underwent a huge boom in Switzerland in the 1990s. So-called compact roundabouts have proved particularly successful with regard to traffic safety; in many cases it was possible to eliminate accident "black spots" by converting existing intersections. Analysis of accident data has shown, however, that safety improvements have not produced satisfactory results at all roundabouts. Indeed, before-and-after comparisons indicate certain roundabouts actually experienced increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
1
9
0
5
Order By: Relevance
“…Furthermore, consistent with Swiss studies (Spacek, 2004), because of the high speeds of the circulating vehicles, the major contributory factor of too large radius of deflection of the approach to the left is associated with angle crashes at entry (S = 6.9%, C = 54.3%, L = 2.61). Consistent with the same Swiss study (Spacek, 2004), which found a negative correlation between the entering-circulating crash rate and the deviation angle, the major contributory factor of a small entry angle is associated with angle crashes at entry (S = 6.2%, C = 41.5%, L = 2.00). The association discovery has also shown that the combination of the major contributory factors radius of deflection and deviation angle is associated with angle crashes at entry (S = 4.7%, C = 32.2%, L = 2.23).…”
Section: Rules For Crash Contributory Factorssupporting
confidence: 77%
See 2 more Smart Citations
“…Furthermore, consistent with Swiss studies (Spacek, 2004), because of the high speeds of the circulating vehicles, the major contributory factor of too large radius of deflection of the approach to the left is associated with angle crashes at entry (S = 6.9%, C = 54.3%, L = 2.61). Consistent with the same Swiss study (Spacek, 2004), which found a negative correlation between the entering-circulating crash rate and the deviation angle, the major contributory factor of a small entry angle is associated with angle crashes at entry (S = 6.2%, C = 41.5%, L = 2.00). The association discovery has also shown that the combination of the major contributory factors radius of deflection and deviation angle is associated with angle crashes at entry (S = 4.7%, C = 32.2%, L = 2.23).…”
Section: Rules For Crash Contributory Factorssupporting
confidence: 77%
“…However, in two approaches, a negative deflection angle is present. Low values of the deflection angle contribute to failures to give way, increased pass-through speeds, and underestimations of these speeds by conflicting parties in the subsequent approach on the right (Spacek, 2004).…”
Section: Geometric Datamentioning
confidence: 95%
See 1 more Smart Citation
“…Selon le ministère des Transports du Québec (2002), il semble qu'un angle de visibilité trop important pourrait nuire au fonctionnement sécuritaire d'un carrefour giratoire car il inciterait les automobilistes à circuler à vitesse plus élevée. La réduction du champ de vision, notamment par l'obstruction de la vision à travers l'îlot central, serait donc né-cessaire pour forcer les automobilistes entrant dans le carrefour giratoire à adopter un comportement prudent et une vitesse convenable (Spacek 2004).…”
Section: Dimensions Et Géométrieunclassified
“…Chaque région doit donc adapter le giratoire à ses propres besoins, ses propres caractéristiques. Ainsi, en Suisse, l'établissement de normes pour la construction des carrefours giratoires s'est appuyé sur une analyse des accidents observés au droit des giratoires au pays (Spacek 2004). Cette analyse a en effet pu mettre en lumière les principales caractéristiques du carrefour giratoire qui permettent son fonctionnement performant et sécuritaire dans l'environnement suisse, soit la déflexion, l'obstruction de la visibilité à travers l'îlot central et le rayon d'entrée.…”
Section: Le Défi De La Conceptionunclassified